(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2007)
New fossil vertebrates from the most representative Upper Pleistocene section (Tyrrhenian, MIS 5e) of the outcrop of San Giovanni di Sinis (Oristano, Sardinia) are here reported and described. The fossils, although scarce and fragmentary, document the occurrence of a terrapin (Mauremys sp.) and the endemic Sardinian deer (Praemegaceros cazioti). Significant is the occurrence of the terrapin because it is the youngest representative of the genus in the central Mediterranean area where it is extinct at present. The Late Pleistocene extinction of Mauremys in Italy follows the same pattern of other Mediterranean reptiles, in being in some cases delayed on the islands. A comparison of the modern range of Mauremys and that of the pond turtle, Emys, as well as of their past ranges as evidenced by the fossil record, might suggest that some sort of thermophily (at least during pre-hatching stages) characterized the former taxon and is responsible for its past and present distribution. SHORT NOTE